Exergy Analysis of Microalgae Thermochemical Conversion using Aspen Plus Simulation - Cholila Tamzysi; Muflih Arisa Adnan; Fadilla Noor Rahma; Arif Hidayat (Dept. of Chemical Engineering, Diponegoro University, 2020)
Microalgae is known as the future bioenergy resources due to its unlimited potential and availability. One of the numerous paths to acquire an energy source is gasification, which produce syngas and methane as a hydrocarbon fuel or feedstock product. To set up an efficient gasification plant, several essential information is needed including the effect of oxidizing agent and steam to carbon (S/C) ratio to energy efficiency on certain biomass properties. This paper aims to study the highest exergy possibility on microalgae gasification process by examining the effect of steam and air flowrate independently via ASPEN Plus simulation. The result was validated with experimental data to verify the simulation reliability. It was found that the thermodynamic based simulation is suitable to predict the reactor behavior and acquire an optimum operating condition.Keywords: microalgae; gasification; exergy; simulation